2018
DOI: 10.1186/s13045-018-0582-8
|View full text |Cite
|
Sign up to set email alerts
|

Next generation of immune checkpoint therapy in cancer: new developments and challenges

Abstract: Immune checkpoints consist of inhibitory and stimulatory pathways that maintain self-tolerance and assist with immune response. In cancer, immune checkpoint pathways are often activated to inhibit the nascent anti-tumor immune response. Immune checkpoint therapies act by blocking or stimulating these pathways and enhance the body’s immunological activity against tumors. Cytotoxic T lymphocyte-associated molecule-4 (CTLA-4), programmed cell death receptor-1 (PD-1), and programmed cell death ligand-1(PD-L1) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
575
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 658 publications
(581 citation statements)
references
References 152 publications
(134 reference statements)
4
575
0
2
Order By: Relevance
“…In this study, we also observed that increased transcriptome levels of CD38, HLA‐DRA, IDO1, and LAG‐3 are significantly correlated with BAP1 loss. These immune biomarkers are of extreme importance because they have been associated with different immune‐suppressive pathways, which suggests mechanistic insights for immune suppression and immunotherapy resistance using ICIs . In the protein single‐cell level, we show the functional state of UM infiltrating CD8 + T cells, which co‐express high levels of CD38, HLA‐DR, and CD28.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, we also observed that increased transcriptome levels of CD38, HLA‐DRA, IDO1, and LAG‐3 are significantly correlated with BAP1 loss. These immune biomarkers are of extreme importance because they have been associated with different immune‐suppressive pathways, which suggests mechanistic insights for immune suppression and immunotherapy resistance using ICIs . In the protein single‐cell level, we show the functional state of UM infiltrating CD8 + T cells, which co‐express high levels of CD38, HLA‐DR, and CD28.…”
Section: Discussionmentioning
confidence: 89%
“…[121][122][123] The expression of immune checkpoints such as TIGIT, TIM3, LAG3 and NKG2A remains poorly characterised in tumor-infiltrating cd T cells and may provide synergistic targets to combine with conventional T-cell targets such as PD-1. As many cd T cells are not MHCrestricted, the co-inhibitory pathways associated with antigen presentation, such as PD-1 and CTLA-4, may be redundant in their tumor recognition.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
“…In addition to CD137, GITR, OX40 and CD27, there are additional costimulatory receptors being targeted for cancer immunotherapy (Cabo, Offringa et al, 2017, Marin-Acevedo, Dholaria et al, 2018). One such receptor is inducible costimulator (ICOS or CD278) which is expressed on activated CD4 + T cells and member of the B7-CD28 family of proteins (Hutloff, Dittrich et al, 1999).…”
Section: Emerging Agonists: Icos and Cd40mentioning
confidence: 99%